Thermal stability of WAlN/WAlON/Al2O3-based solar selective absorber coating. Issue 41 (23rd May 2016) - Dan, Atasi; Chattopadhyay, Kamanio; Barshilia, Harish C.; Basu, Bikramjit
Abstract: The solar absorptance property of W/WAlN/WAlON/Al2 O3 -based coatings, deposited by DC/RF magnetron sputtering on stainless steel substrate was studied by measuring the reflectance spectra in the wavelength range of 250 - 2500 nm. The effect of thermal annealing on the optical properties of the solar selective absorber coatings was investigated. Annealing the coatings at 450°C for 150 hrs in air did not show any significant change in the spectral properties of the absorber coating indicating the excellent thermal stability of the coating. The W layer acts as infrared reflective layer and diffusion barrier on stainless steel substrate. The top Al2 O3 layer serves as dense shield to protect the under layers from oxidation in air. In summary, the present study indicates the potential application of W/WAlN/WAlON/Al2 O3 -based selective coatings in high temperature photo thermal conversion systems.